Feminism and the university: the roles of disciplinary field and educational habitus in the lives and works of two feminist intellectuals - Telling, Kathryn (2013)
This thesis is an exploration of the production of feminist theory as a material, social, and institutional practice: it aims to understand feminist intellectual production as to some extent circumscribed by historical, biographical, political, and especially academic conditions. Specifically, it compares the intellectual trajectories and scholarly output, feminist and otherwise, of theologian Mary Daly (1928-2010) and philosopher Judith Butler (1956--). The analysis tries to keep three aspects of those lives in mind at once: firstly, the properly intellectual character of the intellectuals’ ideas; secondly, the specifically institutional (that is, university) conditions in which they have found themselves; and thirdly, the broader biographical conditions of their lives. By keeping all three in mind at once, we get to a potentially fuller and more nuanced picture of their intellectual trajectories than may be available through critical appraisal of their works alone. The thesis is an original contribution to knowledge both in as much as it brings together Daly and Butler, two apparently fundamentally opposed feminists, in order to see what thinking them together allows us to do, and in the applications and adaptations of Pierre Bourdieu’s social theory which help explain these feminists’ trajectories.